Six months versus nine months anti-tuberculous therapy for female genital tuberculosis: a randomized controlled trial. (August 2016) - Sharma, Jai B.; Singh, Neeta; Dharmendra, Sona; Singh, Urvashi B.; P, Vanamail; Kumar, Sunesh; Roy, K.K.; Hari, Smriti; Iyer, V.; Sharma, S.K.
Abstract: Objective: To compare six months versus nine months anti-tuberculous therapy in patients of female genital tuberculosis. Study design: It was a randomized controlled trial in a tertiary referral center teaching institute on 175 women presenting with infertility and found to have female genital tuberculosis on clinical examination and investigations. Group I women (86 women) were given 9 months of intermitted anti-tuberculous therapy under directly observed treatment short course (DOTS) strategy while Group II (89 women) were given 6 months of anti-tuberculous therapy under DOTS. Patients were evaluated for primary end points (complete cure, partial response, no response) and secondary end points (recurrence rate, pregnancy rate) during treatment. All patients were followed up further for one year after completion of therapy to assess recurrence of disease and further pregnancies. Results: Baseline characteristics were similar between two randomized groups. There was no difference in the complete clinical response rate (95.3% vs 97.7%, p  = 0.441) between 9-months and 6-months groups. Four patients in 9-months group and two patients in 6-months group had recurrence of disease and required category II anti tuberculous therapy ( p  = 0.441). Pregnancy rate during treatment and up to one year follow up was also similar in the two groups (23.2% vs 21.3%, p  = 0.762). Side effects occurred in 27(31.4%) and 29(32.6%) in 9-months and 6-months of therapy and were similar ( p  = 0.866). Conclusions: There was no difference in complete cure rate, recurrent rate and pregnancy rate for either 6-months or 9-months of intermittent directly observed treatment short course anti-tuberculous therapy in female genital tuberculosis. Clinical trial registration: The trial was registered in clinicaltrials.gov with registration no:CTRI/2009/091/001088 .